Application of the Fourier Transform in the determination of diffrac-tion patterns in quasicrystals (SCIÉNDO INGENIUM, 2022)
In this research work the X-rays or electrons quasicrystalline diffraction pattern of a scaled star dodecahedron has been simulated. For this purpose, the fast Fourier transform has been applied to a mass density function that describes the three-dimensional structure constructed from the use of unit cells. Both the network points, the density function, as well as the Fourier fast transform, have been encoded in Fortran programming language. The result is the diffraction pattern with a third-order and fifth-order axis of symmetry, the latter characteristic of quasicrystals icosahedral.